Innovation and Diversity in a Dynamic Knowledge Network. - Sebestyén, Tamás (PTE KTK Műhelytanulmányok, 2022)
In this paper we examine the evolution of network formation. We present a model in which companies in an industry can innovate alone or in alliance with others. Alliance formation is based on the cognitive distance of companies. If two companies form an alliance, their probability of success in innovation depends on their proximity in knowledge space, that is, their cognitive distance. Knowledge, on the other hand, is modelled in two dimensions: breadth and depth. The main results of our analysis are that in the present setting heterogeneity decreases among companies whilst innovation can increase and decrease also, depending on the initial parameters of the industry's knowledge endowment. The model also reveales the importance of external shocks in maintaining heterogeneity and concludes with a possible typology of cluster evolution among the dimensions of heterogeneity and innovativeness.